Adult literacy programs in developing countries - Niels-Hugo Blunch (IZA World of Labor, 2017)
In addition to the traditional education system targeting children and youth, one potentially important vehicle to improve literacy and numeracy skills is adult literacy programs (ALPs). In many developing countries, however, these programs do not seem to achieve these hoped for, ex ante, objectives and have therefore received less attention, if not been largely abandoned, in recent years. But, evidence shows that ALPs do affect other important socio-economic outcomes such as health, household income, and labor market participation by enhancing participants' health knowledge and income-generating activities.
Keywords: I1; I2; I3; J13; J24; O1; 330; adult literacy programs; human capital; literacy and numeracy; income generation; labor market participation; health